"I Didn't Know Massages Could Do That:" A qualitative analysis of the perception of hospitalized patients receiving massage therapy from specially trained massage therapists. (August 2020) - Kelemen, Anne; Anderson, Elizabeth; Jordan, Kerry; Cates, Lauren Cal; Shipp, Gianna; Groninger, Hunter
Highlights: This paper examined the perception and experience of hospitalized palliative care eligible patients receiving massage therapy. Themes identified included peace and relaxation, unique issues related to hospitalization and chronic illness and perceptions of massage experience. Inpatient massage therapy for patients that are palliative care eligible provide patients with a sense of peace companionship rest, coping and connected touch. Abstract: Objective: This study examined the perception and experience of hospitalized palliative care eligible patients receiving massage therapy from specially trained massaged therapist. Design: Twenty hospitalized palliative care eligible patients received three differing doses of massage therapy from specially trained massage therapists. Patients were interviewed about their experience and perception related to the massage. Open-ended data were collected and analyzed using a grounded theory approach. Setting: 912-bed tertiary hospital center in Washington, DC. Results: Participants generally perceived the hospital-based massage experience positively. Participants noted how the massage experience provoked reflection on the overall hospital experience in two ways: first, as a reference point to the inpatient environment itself, and second, in terms of how massage reduces this distress and creates a sense of peace, at least temporarily. Conclusion: The data collected in these semi-structured interviews showed that massage therapy can uniquely ameliorate some of the most pervasive challenges to quality of life for hospitalized patients affected by chronic and serious illness.